Inhibition of GSDMD activation by Z-LLSD-FMK or Z-YVAD-FMK reduces vascular inflammation and atherosclerotic lesion development in ApoE−/− mice - Zhang, Bao-Li; Yu, Peng; Su, En-Yong; Zhang, Chun-Yu; Xie, Shi-Yao; Yang, Xue; Zou, Yun-Zeng; Liu, Ming; Jiang, Hong (Frontiers in Pharmacology, 2023)
Pyroptosis is a form of pro-inflammatory cell death that can be mediated by gasdermin D (GSDMD) activation induced by inflammatory caspases such as caspase-1. Emerging evidence suggests that targeting GSDMD activation or pyroptosis may facilitate the reduction of vascular inflammation and atherosclerotic lesion development. The current study investigated the therapeutic effects of inhibition of GSDMD activation by the novel GSDMD inhibitor N-Benzyloxycarbonyl-Leu-Leu-Ser-Asp(OMe)-fluoromethylketone (Z-LLSD-FMK), the specific caspase-1 inhibitor N-Benzyloxycarbonyl-Tyr-Val-Ala-Asp(OMe)-fluoromethylketone (Z-YVAD-FMK), and a combination of both on atherosclerosis in ApoE−/− mice fed a western diet at 5 weeks of age, and further determined the efficacy of these polypeptide inhibitors in bone marrow-derived macrophages (BMDMs). In vivo studies there was plaque formation, GSDMD activation, and caspase-1 activation in aortas, which increased gradually from 6 to 18 weeks of age, and increased markedly at 14 and 18 weeks of age. ApoE−/− mice were administered Z-LLSD-FMK (200 µg/day), Z-YVAD-FMK (200 µg/day), a combination of both, or vehicle control intraperitoneally from 14 to 18 weeks of age. Treatment significantly reduced lesion formation, macrophage infiltration in lesions, protein levels of vascular cell adhesion molecule-1 and monocyte chemoattractant protein-1, and pyroptosis-related proteins such as activated caspase-1, activated GSDMD, cleaved interleukin(IL)-1β, and high mobility group box 1 in aortas. No overt differences in plasma lipid contents were detected. In vitro treatment with these polypeptide inhibitors dramatically decreased the percentage of propidium iodide-positive BMDMs, the release of lactate dehydrogenase and IL-1β, and protein levels of pyroptosis-related proteins both in supernatants and cell lysates elevated by lipopolysaccharide + nigericin. Notably however, there were no significant differences in the above-mentioned results between the Z-LLSD-FMK group and the Z-YVAD-FMK group, and the combination of both did not yield enhanced effects. These findings indicate that suppression of GSDMD activation by Z-LLSD-FMK or Z-YVAD-FMK reduces vascular inflammation and lesion development in ApoE−/− mice.